Transmylohyoid Submental Intubation in complex maxillofacial trauma: The easiest method is also the safest method - Singh, Ashutosh Kumar; Dulal, Sanad; Yadav, Rajesh; Thapa, Ajay Singh (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Complex maxillofacial trauma is a common occurrence with high velocity road traffic accidents. Multiple facial bone fracture with loss of reference point for bony reduction requires use of intra-operative intermaxillary fixation to obtain good occlusion which precludes oral intubation. Fractures of nasal bones and ethmoid bones with complex distorted anatomy lead to inability to perform a nasal intubation. In such cases sub-mental intubation can be a safe and easy method of securing the intra-operative airway thus avoiding tracheotomy and its complications. Materials & Methods: Retrospective clinical analytical study was planned in which 25 patients were included. Patient’s age, sex, type of trauma, time taken for procedure and complications were taken as study variables. Results: Average time taken for the procedure was nine minutes and only four out of 25 cases had complications. Conclusion: Sub-mental intubation requires simple skills, less time and is relatively complication free compared to tracheotomy in securing intra-operative airway during surgeries for complex maxillofacial trauma. JCMS Nepal. 2016;12(2):55-9